Pancasila Philosophy and Its Contribution to the Development of Golden Indonesia 2045 - Masykur, Zein Muchamad (Jurnal DinamikA, 2024)
It deliverables the role that Indonesia's basic philosophy, Pancasila, has played in carving out the development path of this country since it got its independence. The analysis would be mainly based on content data from some academic articles that deal with legal, political, and social issues in Indonesia, together with an overview of the implantation of Pancasila values into national development. The result of the study shows that Pancasila is very instrumental in guiding the progress and development of the Indonesian state. However, its actualization still faces various challenges, not least lack of public understanding, influence of globalization, and decreased emphasis on education. Optimizing the role of Pancasila towards "Golden Indonesia 2045" would consist of recommendations such as the education of Pancasila values, integration into governance, promotions of religious moderation, involvement of a young generation, and social media optimization. If these challenges are overcome, Pancasila will still be the foundation that underpins Indonesia's progress.